2007
DOI: 10.1103/physrevb.76.214506
|View full text |Cite
|
Sign up to set email alerts
|

Biordered superconductivity and strong pseudogap state

Abstract: Interrelation between the two-particle and mean-field problems is used to describe the strong pseudogap and superconducting states in cuprates. We present strong pseudogap state as off-diagonal short-range order (ODSRO) originating from quasi-stationary states of the pair of repulsing particles with large total momentum (K - pair). Phase transition from the ODSRO state into the off-diagonal long-range ordered (ODLRO) superconducting state is associated with Bose-Einstein condensation of the K - pairs. A checke… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…5,6,7 We show that the SC gap function with a nontrivial nodal line corresponds to a checkerboard pair density wave (PDW) SC state and results in fairly natural explanation of the angle dependence of a partial suppression of the coherent spectral weight in the antinodal region observed by Kondo et al 3 We believe that QPI, other than observed in the nodal region, 2 could be detected in the antinodal one as well. We also show that Kpairing can originate spatial checkerboard pattern without any driving insulating order in contrast to a scenario of a rise of PDW coexisting with a charge density wave (CDW).…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…5,6,7 We show that the SC gap function with a nontrivial nodal line corresponds to a checkerboard pair density wave (PDW) SC state and results in fairly natural explanation of the angle dependence of a partial suppression of the coherent spectral weight in the antinodal region observed by Kondo et al 3 We believe that QPI, other than observed in the nodal region, 2 could be detected in the antinodal one as well. We also show that Kpairing can originate spatial checkerboard pattern without any driving insulating order in contrast to a scenario of a rise of PDW coexisting with a charge density wave (CDW).…”
mentioning
confidence: 57%
“…4 Therefore, in spite of the fact that high-energy QPI is not detected for the present, one can believe that the antinodal region should contribute a coherent state as well. We have argued 5 that both PG and SC states arise exactly in the antinodal region with pronounced nesting of the FC as spatially inhomogeneous incoherent and coherent states of pairs with large momentum, respectively. The nodal region gives rise to conventional SC pairing with zero momentum which, together with the pairing with large momentum (K-pairing) in the antinodal region, forms a biordered SC state in the whole of the Brillouin zone.…”
mentioning
confidence: 94%
“…We have argued 5 that both PG and SC states arise exactly in the antinodal region with pronounced nesting of the FC as spatially inhomogeneous incoherent and coherent states of pairs with large momentum, respectively. The nodal region gives rise to conventional SC pairing with zero momentum which, together with the pairing with large momentum (K-pairing) in the antin-odal region, forms a biordered SC state in the whole of the Brillouin zone.…”
Section: Introductionmentioning
confidence: 94%
“…We would like to summarize here both the early stage [42][43][44][45][46][47][48][49][50][51][52][53] and recent [54][55][56][57][58] theoretical results of the Russian research school in high-TC investigations…”
Section: Figurementioning
confidence: 99%
“…At large values of / J t 2 ³ (which usually are not realized in cuprates) the system becomes unstable towards extended s-wave pairing. For the set electron densities (optimal doping) and the values of / 1/2 J t we get the critical temperature of the d-wave pairing typical for high-TC We would like to summarize here both the early stage [42][43][44][45][46][47][48][49][50][51][52][53] and recent [54][55][56][57][58]…”
Section: Figurementioning
confidence: 99%